A Three Year Music Group for Young Men Recovering from Severe Mental Illness in Northern Ireland - McDougall, Iain (International Journal of Psychosocial Rehabilitation, 2014)
Objective: To describe the rationale, development, implementation and outcomes of a guitar group for young men with psychotic illnesses. Methods: In 2008 a guitar group aimed at young men with psychotic illness was developed by staff of the Rehabilitation and Recovery Team in Limavady, Northern Ireland and continued for 3 years. The group met on a weekly basis to play music together and provide a forum for informal discussion of the patients’ lives and mental health. After three years the men rated their health, mood, self-confidence, motivation, concentration and ability to translate any gains from the group to other aspects of life.Results: The group supported subjective and objective improvements in negative symptoms of Schizophrenia. Improvements in social functioning were observed, the group provided a novel way to engage young men with psychosis in mental health services and the young men wrote, recorded and performed their own music. The group provided a personal learning experience for the staff involved and anecdotal evidence of this is reported.Conclusions and Implications for Practice: This guitar group demonstrated that music is an excellent means to engage young men in services, can improve psychosocial functioning and provides further support for the mental health benefits of music. It challenges the traditional situation of psychiatric review being provided solely in an outpatient clinic.